In situ graphene liquid cell-transmission electron microscopy study of insulin secretion in pancreatic islet cells - Firlar E (Dove Medical Press, 2019)
Emre Firlar,1,2 Meagan Ouy,1 Leigha Covnot,1 Yuan Xing,3 Daniel Lee,1,4 Alessandro Chan,1,4 Yi He,3 Boao Song,2 Solomon Afelik,4 Yong Wang,3 Reza Shahbazian-Yassar,2 Jose Oberholzer,1,3 Tolou Shokuhfar1 1Department of Bioengineering, University of Illinois at Chicago, Chicago, IL, USA; 2University of Illinois at Chicago, Department of Mechanical and Industrial Engineering, Chicago, IL, USA; 3University of Virginia, Department of Surgery, Charlottesville, VA, USA; 4University of Illinois at Chicago, Department of Surgery, Chicago, IL, USA Background: Islet cell transplantation is one of the key treatments for type 1 diabetes. Understanding the mechanisms of insulin fusion and exocytosis are of utmost importance for the improvement of the current islet cell transplantation and treatment of diabetes. These phenomena have not been fully evaluated due either to the lack of proper dynamic imaging, or the lack of proper cell preservation during imaging at nanoscales. Methods: By maintaining the native environment of pancreatic β-cells between two graphene monolayer sheets, we were able to monitor the subcellular events using in situ graphene liquid cell (GLC)-transmission electron microscopy (TEM) with both high temporal and high spatial resolution. Results: For the first time, the nucleation and growth of insulin particles until the later stages of fusion were imaged at nanometer scales. The release of insulin from plasma membrane involves the degradation of plasma membrane and drastic reductions in the shorter axis of the insulin particles. Sequential exocytosis results indicated the nucleation, growth and attachment of the new insulin particles to the already anchored ones, which is thermodynamically favorable due to the reduction in total surface, further reducing the Gibbs free energy. The retraction of the already anchored insulin toward the cell is also monitored for the first time live at nanoscale resolution. Conclusion: Investigation of insulin granule dynamics in β-cells can be investigated via GLC-TEM. Our findings with this technology open new realms for the development of novel drugs on pathological pancreatic β-cells, because this approach facilitates observing the effects of the stimuli on the live cells and insulin granules. Keywords: transmission electron microscopy, graphene liquid cell, insulin secretion, exocytosis